Eksplorasi Konsep Fisika pada Teknologi dan Aktivitas dalam Kehidupan Sehari-hari - D R Maghfiroh; N M E Rossa; R A Safitri; Dwikoranto Dwikoranto; N A Lestari (Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya, 2022)
This study aims to determine the concepts of physics used in technology and daily life, to find out photos that can provide information to readers and know the study of photos related to the concepts of physics. In this article, the experimental method carried out is in the form of obtaining material, observing the object to be taken, and taking pictures. This article obtained five physics concepts contained in the photo, namely the concept of Boyle's law, the concept of Newton's I law, the concept of circular motion, the concept of static electricity, and the concept of the Doppler effect. In everyday life, there are many phenomena related to physics concepts, such as the condition of a syrup bottle equipped with a pump related to Boyle's law concepts. This child is cycling, related to Newton's First Law concepts and the concept of circular motion, a mouse-repellent device, related to the Doppler effect and the occurrence of static electricity when combing hair and sticking small papers on a plastic ruler. From this article, it can be concluded that many phenomena in everyday life are related to the concepts of physics, including the concepts of Boyle's law, Newton's first law, circular motion, static electricity, and the Doppler effect. Keywords: concepts exploration, physics, photo, technology